1977
DOI: 10.1111/j.1432-1033.1977.tb11410.x
|View full text |Cite
|
Sign up to set email alerts
|

4‐Amino‐hex‐5‐enoic Acid, a Selective Catalytic Inhibitor of 4‐Aminobutyric‐Acid Aminotransferase in Mammalian Brain

Abstract: Incubation of rat brain 4-aminobutyrate aminotransferase with 4-amino-hex-5-enoic acid, a substrate analog of 4-aminobutyric acid, results in a time-dependent irreversible loss of enzymatic activity. In the presence of 0.1 mM inhibitor the half-life of the inactivation process is approximately 6 min. Low concentrations of L-glutamic acid or 4-aminobutyric acid protect against this inactivation, while 2-oxoglutarate prevents this protection, suggesting that only the pyridoxal form of the enzyme is susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(129 citation statements)
references
References 19 publications
4
125
0
Order By: Relevance
“…Vigabatrin (y-vinyl GABA or GVG) is a selective, enzyme-activated, irreversible inhibitor of GABAtransaminase (15,18), the enzyme primarily responsible for the catabolism of y-aminobutyric acid (GABA), a major inhibitory neurotransmitter in the mammalian central nervous system. Animal studies have shown that elevation of brain GABA by this mechanism can prevent experimental seizures (2 1- 23,29), and clinical trials have shown vigabatrin to have beneficial eKects in 'certain types of drug re-sistant or uncontrolled epilepsy (4,8,20,26,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Vigabatrin (y-vinyl GABA or GVG) is a selective, enzyme-activated, irreversible inhibitor of GABAtransaminase (15,18), the enzyme primarily responsible for the catabolism of y-aminobutyric acid (GABA), a major inhibitory neurotransmitter in the mammalian central nervous system. Animal studies have shown that elevation of brain GABA by this mechanism can prevent experimental seizures (2 1- 23,29), and clinical trials have shown vigabatrin to have beneficial eKects in 'certain types of drug re-sistant or uncontrolled epilepsy (4,8,20,26,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…A superficial section (less than 0.2 g) of the left temporal lobe of the cerebrum was removed within 3-4 min after exsanguination of anesthetized dogs and quickly frozen in liquid nitrogen. These samples were stored frozen at -80°C until assayed for GABA, GABA-T, and GAD (glutamate decarboxylase) according to methods previously used for brains of mice, rats, and monkeys (18)(19)(20)(21). GAD is the enzyme responsible for the synthesis of GABA in GABAergic neurons (12,20 (34), which included effects of sex and week of sacrifice.…”
Section: Introductionmentioning
confidence: 99%
“…As GABA-AT is a key enzyme involved in the GABA metabolic pathways and GABA shunt, the inhibitors of this enzyme can increase the level of GABA, and have a potency to cure some diseases derived from the decrease of GABA. After vigabatrin was used as an irreversible GABA-AT inhibitor to cure epilepsy in clinic [18] , many other GABA analogs were synthesized for the inhibitory evaluation of GABA-AT [16,[19][20][21][22][23][24][25][26][27] . Moreover, gabaculine, a naturally occurring neurotoxin produced by the bacteria Streptomyces toyocaensis No.…”
Section: Discussionmentioning
confidence: 99%